Analysis of the active components and mechanism of Shufeng Jiedu capsule against COVID-19 based on network pharmacology and molecular docking. Issue 1 (7th January 2022) - Simayi, Jimilihan; Nuermaimaiti, Maimaitiming; Wumaier, Ainiwaer; Khan, Nawaz; Yusufu, Maierdan; Nuer, Muhadaisi; Maihemuti, Nulibiya; Bayinsang,; Adurusul, Kaysar; Zhou, Wenting
Abstract : Abstract: This study investigates the active components and mechanism of Shufeng Jiedu Capsules (SFJDC) against novel coronavirus through network pharmacology and molecular docking. The TCMSP, TCMID, and BATMAN-TCM databases were used to retrieve the components of SFJDC. The active components were screened by ADME (absorption, distribution, metabolism, and excretion) parameters, and identified by Pubchem, Chemical Book, and ChemDraw softwares. The molecular docking ligands were constructed. SARS Coronavirus-2 Major Protease (SARS-CoV-2-M pro ) and angiotension converting enzyme 2 (ACE2) were used as molecular docking receptors. AutoDock software was used for molecular docking. Cytoscape 3.7.1 software was used to generate an herbs-active components-targets network. Gene Ontology gene function and Kyoto Encyclopedia of Genes and Genomes signal pathway analysis were performed by DAVID data. A total of 1244 components were identified from SFJDC, and 210 active components were obtained. Among them, 97 active components were used as docking ligands to dock with SARS-CoV-2-M pro and ACE2. There were 48 components with good binding activity to SARS-CoV-2-M pro . Ten active components (including 7-Acetoxy-2-methylisoflavone, Kaempferol, Quercetin, Baicalein, Glabrene, Glucobrassicin, Isoglycyrol, Wogonin, Petunidin, and Luteolin) combined with SARS-CoV-2-M pro and ACE2 simultaneously. Among them, Kaempferol, Wogonin, and Baicalein showed higher binding activity. The herbs-active components-targets network contained 7 herbs, 10 active components, and 225 targets. The 225 target targets were involved in 653 biological processes of Gene Ontology analysis and 130 signal pathways (false discovery rate ⩽ 0.01) of Kyoto Encyclopedia of Genes and Genomes analysis. The active components of SFJDC (such as Kaempferol, Wogonin, and Baicalein) may combine with ACE2 and act on multiple signaling pathways and targets to exert therapeutic effect on novel coronavirus.